1992
DOI: 10.1016/0168-1923(92)90076-g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil surface temperature on the growth of millet in relation to the effect of Faidherbia albida trees

Abstract: The effect of soil surface temperature on the growth of millet in relation to the effect of Faidherbia albida trees. Agric. For. Meteorol., 60: 93-100.Faidherbia albida is an important tree species in traditional agroforestry cropping systems o f the Sahel. The enhanced crop growth under its canopy (the 'albida effect') has been attributed to increased soil fertility in the canopy zone, improved microclimate, particularly in relation to plant/soil water relations, and the fact that the tree sheds its leaves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 4 publications
1
16
0
2
Order By: Relevance
“…In the SAT savanna of Kenya, baobab and Acacia tortilis trees reduced soil temperature under their crowns by 6 °C at 5 cm and 10 cm depth, compared with open areas (Belsky et al, 1993). In the Sahel, faidherbia trees lowered soil temperature at 2-cm depth by 5°to 10 °C depending on the movement of shade (Vandenbeldt and Williams, 1992). Soil temperatures in the Sahel often reach lethal levels of 50°to 60 °C at the beginning of the rainy season, causing poor establishment of millet (Soman et al, 1987).…”
Section: Microclimatementioning
confidence: 99%
See 2 more Smart Citations
“…In the SAT savanna of Kenya, baobab and Acacia tortilis trees reduced soil temperature under their crowns by 6 °C at 5 cm and 10 cm depth, compared with open areas (Belsky et al, 1993). In the Sahel, faidherbia trees lowered soil temperature at 2-cm depth by 5°to 10 °C depending on the movement of shade (Vandenbeldt and Williams, 1992). Soil temperatures in the Sahel often reach lethal levels of 50°to 60 °C at the beginning of the rainy season, causing poor establishment of millet (Soman et al, 1987).…”
Section: Microclimatementioning
confidence: 99%
“…Competition for light is unlikely to be a major factor under faidherbia because of its 'reverse phenology' of dropping leaves at the beginning of the rainy season (Vandenbeldt and Williams, 1992), nor under prosopis because of heavy lopping of foliage during the dry season for livestock feeding (Tejwani, 1994). However, shade could be a major problem under large, unmanaged, evergreen trees such as néré, karité, A. nilotica and mango.…”
Section: Competition For Growth Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Sahel, temperatures are already close to the maximum for plant growth, especially at the starting of the season. Experiments with different levels of shading showed that temperature has a pronounced effect on millet production in the Sahel (Vandenbeldt and Williams, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Buffering agricultural crops against water deficiencies is, therefore, an important function that agroforestry would have to play in the adaptation battle, but there are also other mechanisms such as improved micro-climate and reduced evapotranspiration through which agroforestry practices may improve the adaptive capacity of agroecosystems in the occurrence of extreme climate. For example, a study on a Faidherbia albida -millet parkland system in Niger demonstrated that shade-induced reduction of soil temperatures, particularly at the time of crop establishment, contributes to the better growth of millet under trees (Vandenbeldt and Williams, 1992). Also, Jonsson et al (1999) measured temperatures, photosynthetically active radiation (PAR) and millet biomass under and away from tree canopies in a parkland system.…”
Section: Enhancing Adaptive Capacity Through Agroforestrymentioning
confidence: 99%